Pengaruh Dana Pihak Ketiga dan Non Perfoming Loan Terhadap Penyaluran Kredit di Masa Pandemi pada BPD di Pulau Jawa - Oktaviani Rarassati; Rosma Pakpahan; Setiawan Setiawan (Indonesian Journal of Economics and Management, 2022)
This study aims to determine the effect of Third Party Funds and Non-Performing Loans during the pandemic at Regional Development Banks in Java for the 2020-2021 Period. The research method used is descriptive and uses a quantitative approach. The data used are secondary data in the form of Financial Services Authority. The number of samples used in this study were four Regional Development Banks in Java. The technique for sampling is the purposive sampling technique. The analytical technique used in this study is panel data regression analysis using the Eviews 10 program tool. Based on the results and interpretations that partically the Third Party Fund variable has a positive and significant effect to Credit Distribution and the Non-Performing variable has a negative and significant impact to Credit Distribution and Third Party Funds and Non-Performing Loans simultaneously have an effect significant to Credit Distribution.